Manual vs. Mechanical Ventilation in Respiratory Parameters of intubated Patients During cardiopulmonary Resuscitation; a Randomized Clinical Trial - Lotfi, Nastaran; Bagheri Moghaddam, Ahmad; Froutan, Razieh; Nezami, Hossein (Archives of Academic Emergency Medicine, 2025)
Introduction: Ventilation and oxygen delivery during cardiopulmonary resuscitation (CPR) is of paramount importance. This study aimed to compare the effects of manual and mechanical ventilation on respiratory parameters of intubated patients during CPR. Methods: This randomized controlled clinical trial was conducted in 2024 on 61 intubated patients with neurological disorders admitted to the ICU of educational hospitals. Participants were allocated to either the intervention or the control group using block randomization with a block size of six. The intervention group received mechanical ventilation, while the control group received manual ventilation using bag valve mask (BVM). The effects of manual versus mechanical ventilation during CPR on key physiological and respiratory parameters, including venous blood gases (VBG), end tidal Co2 (ETCO₂), and peripheral oxygen saturation (SpO₂) were compared between groups. Statistical analyses were performed using SPSS version 21. Results: The study findings indicated no statistically significant differences between the manual and mechanical ventilation groups in terms of venous blood pH levels (P = 0.38), PCO2 (P = 0.65), and HCO3 levels (P = 0.47) changes. However, PO₂ (P < 0.001), ETCO₂ (P < 0.05). and SpO₂ (P < 0.001) were more stable and consistently higher in patients receiving mechanical ventilation. Conclusion: These findings suggest that while pH, PCO₂, and HCO3 levels did not significantly differ between the two ventilation methods, mechanical ventilation demonstrated superior efficacy in optimizing oxygenation (PO₂ and SpO₂) and regulating ETCO₂ levels.